KAJI EKSPERIMENTAL DAN NUMERIK KARAKTERISTIK PENUKAR KALOR KOMPAK DENGAN CAMPURAN AIR-ES (ICE SLURRY) SEBAGAI FLUIDA PENDINGIN - R., Iskandar
The combination of sensible and latent heat transfer takes place as long as ice consisting in a phace change fluid from solid to liquid. This research investigate how far the influence adding of ice in cooling fluid to heal transfer parameters in a compact heat exchanger. this mixture of water-ice is called ice shiny. Because a temperature difference between cold fluid with hot fluid becomes higher, the results of research show that heat iranfer with a phase change at cold fluid can increase heat transfer from hot fluid. From the research doing for some mass flow rate of fluid freezer, the difference of ice shiny heat transfer with cold water in temperature 0Â° Celsius is about 14 - 2R % of energy which can he given by ice. And heat transfer increases in 42-61 % if it is compared with water which has temperature near by the outlet temperature of chiller system. The research is also done in a theoritical calculation by mathematic modeling and numerical method. which can be repealed for different input data quickly. And program designed is good enough to he used in analyzing a compact heat exchanger.